Relationship of Fast Food Consumption, Physical Activity and Stress Level with The Degree of Primary Dysmenorhore Pain - Khairunnisa; Sajiman; Anwar, Rosihan (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
The prevalence of primary dysmenorrhea in Indonesia is 54.89%. Primary dysmenorrhea has a major impact on school-aged adolescents because it disrupts daily activities. Based on UKS data from January to June 2023, 7.8% of female students visited because of menstrual pain. This research was conducted to determine the relationship between fast food consumption, physical activity and stress levels with the degree of primary dysmenorrhea. This type of research is analytical observational using a cross sectional design. The research was carried out at SMPN 1 Kandangan with a population of 178 and a sample of 45 female students, taken using a simple random sampling method using a spinner tool Data on the degree of dysmenorrhea were obtained through a questionnaire, stress levels through the PSS-10 questionnaire, fast food consumption through interviews using the SQ-FFQ questionnaire and physical activity obtained through the PAL questionnaire. Data analysis used the Spearman Rank correlation test. This research shows that 40% of female students experience grade 1 dysmenorrhea, 57.8% have the habit of frequently consuming fast food, 46.7% have moderate physical activity and 53.3% experience moderate levels of stress. There is a relationship between fast food (ρ = 0.012), physical activity (ρ = 0.002) and the degree of primary dysmenorrhea and there is no relationship between stress levels (ρ = 0.654) and the degree of primary dysmenorrhea.